New Land Use Management Initiative (NIGEUS) for smallfarms in north-central Nicaragua - García Lozano, Carla (2026)
Nicaraguan small farmers produce more than 80 % of the country’s food and face challenges that affect their economic well-being and are vulnerable to climate and environmentalrisks. This paper analyzes eight Soil Management Initiatives (IGEUS) and fromthem, 25 key indicators have been extracted for the design of a survey that allowed collectinginformation on soil management in 455 farms located in the municipalities of El Tuma-La Dalia, El Cuá and Waslala, in Nicaragua, to analyze them from a sustainable perspective. The results reveal the need to strengthen practices based on ecosystemic, integral, holistic, gender equality and participatory approaches. A new initiative for sustainable land management and use (NIGEUS) emerges from our findings and itsapplicability will depend on an assessment of the stakeholders